2018
DOI: 10.2152/jmi.65.131
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antigen‐positive toxin‐negative enzyme immunoassay results for the diagnosis of toxigenic Clostridium difficile infection

Abstract: Clostridium difficile (C. difficile)-associated diarrhea (CDAD) is a challenging nosocomial infectious disease. C. DIFF Quik Chek Complete assay is widely used to detect glutamate dehydrogenase (GDH) antigen and toxin A/B of C. difficile simultaneously. However, the interpretation of GDH positive/toxin negative results is problematic. We performed a retrospective study of patients with GDH positive/toxin negative results to determine the probability of detecting toxigenic C. difficile and its risk factors. Bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Given the prevalence of low-toxin strains in clinical settings, both in our study and in other reports [11,38,58], failure to detect toxin in the stool of C. difficile -positive patients should be interpreted with caution. In their study, Reigadas et al reported 12.7% of CDI cases (n = 26 of 204 total) would have been missed due to a lack of clinical suspicion despite these patients exhibiting mild-to-moderate symptoms [59].…”
Section: Discussionmentioning
confidence: 58%
“…Given the prevalence of low-toxin strains in clinical settings, both in our study and in other reports [11,38,58], failure to detect toxin in the stool of C. difficile -positive patients should be interpreted with caution. In their study, Reigadas et al reported 12.7% of CDI cases (n = 26 of 204 total) would have been missed due to a lack of clinical suspicion despite these patients exhibiting mild-to-moderate symptoms [59].…”
Section: Discussionmentioning
confidence: 58%
“…Our findings indicate that up to 69% of the GDH+/Toxin-specimens nevertheless harbor toxigenic C. difficile. Similarly, Akamatsu et al reported toxigenic C. difficile to be present in 63.2% of GDH+/Toxin-specimens (45). The CDC estimates that discrepant specimens (NAAT+/Toxin-) constitute 31% of the national sampling set (25), although regional differences may be masked in national averages.…”
Section: Discussionmentioning
confidence: 99%
“…In our study in 16% the samples, GDH was positive without toxin production. In a study done by Akamatsu et al 24 , out of the 356 GDH positive/ toxin negative patients, cultures were done in 220 samples and toxin producing C. difficile was obtained from 139 (63.2%) samples. 24 Therefore such population who are GDH positive/toxin negative, should be monitored carefully.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by Akamatsu et al 24 , out of the 356 GDH positive/ toxin negative patients, cultures were done in 220 samples and toxin producing C. difficile was obtained from 139 (63.2%) samples. 24 Therefore such population who are GDH positive/toxin negative, should be monitored carefully. Also, the effect of C. difficile colonization varies in different patients (asymptomatic carrier state to fulminant colitis and death).…”
Section: Discussionmentioning
confidence: 99%